ACHIEVEMENT OF MONUMENTALITY INDICATORS AND PREFERENCES OF TWO GENERATIONS GROUPS ON HISTORICAL MONUMENTS IN JAKARTA - Aghastya Wiyoso; Wegig Murwonugroho; Deddy Wahjudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
ABSTRACT Monumentality is the quality of buildings and monuments, the achievements of which help shape the identity of the place they exist. As a landmark, the object is indicated monumental through several potentials it has. One historical monument in Jakarta, the National Monument (Monas), which have an important historical record in the development of Jakarta City during the Soekarno’s era and has survived to this day, is significant to study how to fulfill their monumentality indicators not only to strengthen and build public perception of their monumental achievements but also to support strategic plans that can be carried out in the future. The research applies a combined method; qualitative and quantitative approaches. Qualitative research was carried out with theoretical testing regarding the fulfillment of the old and new monumentality indicators on this monument, strengthened through interviews with experts. Quantitative research was conducted to measure the preferences of respondents who were categorized as millennial and pre-millennial groups towards the object of research based on their recall potential or memorability. The potential for remembrance was chosen because it is the perennial essence of monumentality. The results of the study show that the achievement of indicators of monumentality and respondent's preference for the research object, the highest is occupied by Monas, surpasses the achievements of other monuments within the same category and is also well recognized by the Millenials, not much different from the older generation (pre millenial). There are several points of monumentality indicators that have not been met, especially from the new paradigm, but looking at the facts of the overall achievements of Monas, it can be affirmed that the indications of devaluation of monuments that fail to respond to the needs of their time and society are not proven.